Implementasi Pancasila Sebagai Entitas Dan Identitas Pendidikan Abad Ke-21 Di SMAN 4 Palangka Raya - Yulina Mingvianita; Halimah Halimah; Misnawati Misnawati; Stefani Ratu Lestariningtyas; Sepmiatie Sepmiatie; Ratni Indah Suryatini (Universitas 45 Surabaya, 2023)
This research was made for the purposes of: (1) The challenge of living Pancasila as the entity and identity of the Indonesian nation, the embodiment of the Pancasila student profile in education that is pro-student in 21st century education, (2) to describe the implementation of Pancasila as the entity and identity of the Indonesian nation and its embodiment. Pancasila student profiles in education that are pro-students in 21st century education in the school ecosystem (class). This study uses qualitative research with observation methods conducted at SMA Negeri 4 Palangka Raya. The observation method is a data collection method that is carried out by observing objects directly, by being involved (participatory) or without involving. The techniques used in this research are surveys and interviews in collecting data related to the implementation of Bhineka Tunggal Ika values and Pancasila values in schools. Research data were analyzed descriptively. The results of the study show that: (1) the challenges of living Pancasila as an entity and identity of the Indonesian nation are revealed, the embodiment of the profile of Pancasila students in education that is pro-student in 21st century education, namely the influence of foreign culture, the lack of role and attention of parents towards their children, and the influence of the social environment of students. (2) It was revealed that SMA Negeri 4 Palangkaraya has implemented Pancasila as the entity and identity of the Indonesian nation and the embodiment of the Pancasila student profile in Education which is pro-student in 21st century education in the school ecosystem (class).